2010
DOI: 10.1111/j.1365-2125.2010.03665.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching of clinical pharmacology and therapeutics in UK medical schools: current status in 2009

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Junior doctors feel poorly prepared by their training in Clinical Pharmacology and Therapeutics and commonly make prescribing errors. • Since 1993 the General Medical Council's guidance on undergraduate medical education ‘Tomorrow's Doctors’ has emphasized the integration of Clinical Pharmacology and Therapeutics teaching within the medical curriculum. • With the publication of a new version of Tomorrow's Doctors in 2009, medical schools will be further revising thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 9 publications
2
73
2
Order By: Relevance
“…Additionally, we excluded private medical schools because their education is not accessible for all students. A 24‐item web‐based questionnaire (using surveymonkey.com) was developed, based on comparable studies,7, 8, 9, 26 and validated by the Education Working Group of the EACPT during an online modification round ( Supplementary Material Figure 1 ). The questionnaire asked specific questions about undergraduate teaching and assessment of basic pharmacology, clinical pharmacology and therapeutics, and the preparedness of students for their future task as prescribers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we excluded private medical schools because their education is not accessible for all students. A 24‐item web‐based questionnaire (using surveymonkey.com) was developed, based on comparable studies,7, 8, 9, 26 and validated by the Education Working Group of the EACPT during an online modification round ( Supplementary Material Figure 1 ). The questionnaire asked specific questions about undergraduate teaching and assessment of basic pharmacology, clinical pharmacology and therapeutics, and the preparedness of students for their future task as prescribers.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, a survey conducted under the auspices of the World Health Organization (WHO) in 1988 showed that European medical schools devoted relatively little time to teaching clinical pharmacology and that there was a lack of trained individuals in this area 7. However, it is not known whether the situation has improved in the meantime, although recent studies showed marked differences in the quality and quantity of CPT teaching and training between medical schools in the same country 8, 9. Although these findings are worrying, a new baseline evaluation is needed to serve as a starting point for a harmonized CPT curriculum throughout the EU, as suggested by the British Pharmacological Society (BPS) and European Association of Clinical Pharmacology and Therapeutics (EACPT) in 2007 3.…”
mentioning
confidence: 99%
“…Hence, a major point for improvement is the assessment procedure, which may also improve learning efficiency [28]. In earlier studies, this loss of the explicit assessment procedure was already described for the UK after the introduction of the PBL [14,15]. Internationally, PBL or related teaching strategies are now the main teaching strategy in medical education [29], although another study describes that PBL introduction depends on culture and that on average, southern European countries had lower percentages of medical schools with PBL, at least in 2008 [30].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, O'Shaughnessy et al found large differences between UK medical schools in the content, learning strategies, and assessment procedures of curricula. In most medical schools, pharmacology and pharmacotherapy education was integrated vertically and/or horizontally [15]. However, given that most medical schools are still changing their curricula, these studies are probably out of date.…”
Section: Introductionmentioning
confidence: 99%
“…In BTomorrow's Doctors,^the General Medical Council's guidance on undergraduate medical education emphasized the importance of integrating clinical pharmacology and therapeutics teaching within the medical school curriculum [3]. Overall, it seems clear that pharmacology education in the medical school curriculum must improve, as insufficient knowledge about commonly used medications or the confidence to apply this knowledge will make it difficult for our future physicians to provide safe and effective patient care.…”
mentioning
confidence: 99%